(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The 73rd Constitutional Amendment was passed in the hopes that it would improve governanceand give political space to groups that have historically faced discrimination, such as women, schedulecastes, and schedule tribes. Panchyati Raj institutions have long been seen as a means to goodgovernance. The goal of the current research was to understand the position of women in Panchayat rajand the issues they encounter.